The Difference of Incidence of Pulp Necrosis with Chronic Apical Abscess among Hypertensive and Normotensive Patients in Dr. Moewardi Hospital - Andrio Palayukan; Risya Cilmiaty; Marwoto . (Nexus Kedokteran Klinik, 2015)
Backgrounds: Pulp necrosis is a continuation of pulp inflammation that did not receive adequate treatment. Necrotic pulp along with bacteria growing in the vicinity can cause an inflammatory response in the periapical tissues. The aim of this study was to determine the difference of incidence of pulp necrosis with chronic apical abscess between hypertensive and normotensive patients at Dr.Moewardi Hospial. Methods: The design of this study was case control with cross sectional approach. Data were collected from medical record of patient at dental outpatient clinic Dr. Moewardi Hospital from September 2013 to September 2014. Samples were taken by purposive sampling method. Samples were classified into four groups: patient with hypertension and pulp necrosis with chronic apical abscess, hypertension and dental caries, normotensive and pulp necrosis with chronic apical abscess, normotensive and dental caries. Data were analyzed by Chi Square test (? = 0.05). Result: There were 70 Subjects who met inclusion and exclusion criteria. The percentage of hypertensive and pulp necrosis with chronic apical abscess was 24.28%, hypertensive and dental caries was 2.86%, normotensive and pulp necrosis with chronic apical abscess was 40%, and normotensive with dental caries was 32.86%. The result of Chi Square test demonstrated a significant difference between the four groups with p = 0.007 (p < 0.05). Conclusion: There is a significant difference of incidence of pulp necrosis with chronic apical abscess between hypertension and normotensive patients at Dr. Moewardi Hospital. Key words: pulp necrosis, chronic apical abscess, hypertensive, normotensive